Magnetic properties of the triangular-lattice antiferromagnets Ba3RB9O18 (R = Yb, Er) - Khatua, Joydev; Pregelj, M.; Elghandour, Ahmed; Jagličic, Z.; Klingeler, Rüdiger; Zorko, A.; Khuntia, P. (Physical review, 2022)
Frustration-induced strong quantum fluctuations, spin correlations, and interplay between competing degrees of freedom are some of the key ingredients that underlie exotic states with fractional excitations in quantum materials. Rare-earth-based two-dimensional magnetic lattices possessing a crystal electric field, spin-orbit coupling, anisotropy, and electron correlation between rare-earth moments offer a new paradigm in this context. Herein, we present crystal structure, magnetic susceptibility, and specific heat results accompanied by crystal electric field calculations on polycrystalline samples of Ba3RB9O18 (R=Yb, Er), in which R3+ ions form a perfect triangular lattice.
Im Titel erscheinen die Ziffern 3, 9 und 18 tiefgestellt
Gesehen am 29.11.2022